Chromosomal Aberrations in Blood Lymphocytes as Predictors of Respiratory Function After Stereotactic Lung Irradiation - Kocsis, Zsuzsa S.; Farkas, Gyöngyi; Bajcsay, András; Kun-Gazda, Márta; Lövey, József; Ostoros, Gyula; Pócza, Tamás; Herein, András; Ladányi, Katalin; Székely, Gábor; Markóczy, Zsolt; Takácsi-Nagy, Zoltán; et al. (Frontiers in Oncology, 2022)
Due to the profound difference in radiosensitivity of patients and various side effects caused by this phenomenon, a radiosensitivity marker is needed. Prediction by a marker may help personalise the treatment. In this study, we tested chromosomal aberrations (CA) of in vitro irradiated blood as predictor of pulmonary function decrease of non-small cell lung cancer (NSCLC) patients and also compared it to the CAs in the blood of irradiated patients. Peripheral blood samples were taken from 45 lung cancer patients before stereotactic radiotherapy (SBRT) and immediately after the last fraction and 3, 6, 9, 12, 15, 18, 21 and 24 months later. Respiratory function measurements were performed at the same time. Diffusing capacity of lung for carbon monoxide (DLCO), Forced vital capacity (FVC), Forced expiratory volume in one second (FEV1s) and FEV1s/FVC (FEV1%) were monitored. Metaphase preparations of lymphocytes were made with standard procedures, and chromosome aberrations were analysed. In our cohort, the 36-month local relapse free survival was 97.4%, and the distant metastasis free survival was 71.5% at 36 months. There was no change in the mean of the pulmonary function test (PFTs) after the therapy. However, there was a considerable variability between the patients. Therefore, we subtracted the baseline and normalised the PFT values. There were significant decreases at 12-24 months in relative FEV1s and relative FEV1%. The tendentious decrease of the PFTs could be predicted by the in vitro chromosome aberration data. We also found connections between the in vitro and in vivo CA values (i.e. dicentrics plus rings after 3 Gy irradiation predicts dicentric plus ring value directly after the radiotherapy/V54Gy. (p=0.001 24.2%)). We found that - after further validation - chromosome aberrations resulted from in vitro irradiation before radiotherapy can be a predictive marker of pulmonary function decrease after lung irradiation.